AI-Enhanced Structured Literacy Intervention for Secondary Students: A Case Study of Science of Reading - Bird, Jennifer; Gupta, Abha (International Journal of Educational Studies, 2025)
This study examines the effectiveness of Lexia PowerUp, an AI-powered literacy program, for sixth-grade students requiring Tier 3 reading intervention. Seven sixth-grade students (six boys, one girl; five African American, two Caucasian; all qualifying for free/reduced lunch) participated in a six-month intervention combining 50 minutes of daily small-group instruction with individualized Lexia PowerUp usage. Researchers measured progress through Achieve 3000 Lexile assessments and Lexia PowerUp performance data across three skill strands: Word Study, Grammar, and Comprehension. All participants demonstrated Lexile level improvements from beginning-of-year to mid-year assessments, though students remained below sixth-grade benchmarks (925-1070L). Analysis of Lexia PowerUp progression showed movement from foundational to intermediate levels, with 50% of students advancing in Word Study and 75% reaching intermediate level in Comprehension (up from 63%). However, all students remained at foundational level in Grammar throughout the study period. Individual progress varied considerably across strands, with some students gaining over 100 units in specific areas while showing minimal growth in others. The study highlights potential benefits of combining AI-driven adaptive learning with teacher-led instruction for struggling secondary readers, though results indicate continued need for intensive support to achieve grade-level proficiency. This study addresses the understudied population of Tier 3 secondary readers by examining AI-powered reading intervention specifically for sixth-grade students requiring the most intensive literacy support, an area with limited empirical research.